The Impact of Corporate Financial Disclosure Quality on Banks’ Loan Risk Assessment: A Case Study of Uzbekistan - Akhmedov, Behruz (European Scientific Journal, ESJ, 2025)
In developing economies such as Uzbekistan, financial reporting of corporations is crucial in helping the banks to assess the risk of loan borrowers. These disclosures are especially important as they determine the capacity of the financial institutions to assess the creditworthiness of the businesses. The paper at hand examines the efficacy of corporate financial disclosures and their influence on the risk assessment process of banks in the Uzbekistan country, which is in the process of the transition to the market-based economy with a developing regulation process. Based on recent research, this study will analyze the effects of financial transparency and the quality of financial reporting on the credit risk management capability of banks and their capacity to make proper decisions on lending. The banking industry of Uzbekistan has experienced significant reforms, such as the implementation of the International Financial Reporting Standards (IFRS) and the guidelines on risk-based supervision introduced by the Central Bank (Khasanovich, 2025; Kadirovich & Rabbimovich, 2021). Still, there are some problems with the quality and timeliness of corporate financial reporting, which may impede the proper assessment of risks. As an example, Khushnud and Qingjie (2020) emphasize that the financial reporting discrepancies undermine banks in their attempt to efficiently assess the risk of small and medium enterprises (SMEs) in Uzbekistan, which is a principal part of the economic growth (Burkhanov, 2023). The use of IFRS is viewed as a step toward enhancing the comparability and reliance of financial reports, but the full shift to the new system remains under development (Mamadiyarov et al., 2024). In addition, the transition to digitalization of the banking sector, as Khamdamov et al. (2024) write, presents new prospects of increasing the effectiveness of credit decisions, which may lead to the elimination of the use of unreliable financial information. It is also noted in this study that there should be improved regulatory control and the introduction of international accounting standards to increase financial transparency, which would help improve risk evaluation (Tadjibaeva, 2019). The paper brings out its conclusion by providing suggestions to the policymakers and banks in Uzbekistan on how they can improve the efficacy of the corporate financial disclosures in reducing credit risks and encouraging a more balanced financial background.